Estudio comparativo de las ventas en Altec S.A., periodo 2019 – 2020. Cantón Babahoyo. - Amat Cabrera, Pedro Samuel (2022)
Altec S.A. aluminum and glass, with Unique Taxpayer Registry No. 0991366059001. Using analytical, historical and descriptive methodology, this Case Study is named "COMPARATIVE STUDY OF SALES IN ALTEC S.A., PERIOD 2019 - 2020. BABAHOYO CANTON". In Ecuador there are institutions that are dedicated to the manufacturing service and the installation of glass, aluminum, and wood window and door systems, this in order to preserve the safety of homes with the best manufacturing tools for home design. The main objective of the investigative work is to compare, through the observation technique, the effects on sales and their impact on the company Altec S.A. 2019-2020 period, using the horizontal and vertical financial analyzes applied to the financial statements. This financial analysis was applied to the Statement of Comprehensive Income or also known as the profit or loss statement. In the financial analysis that was applied to the Income Statement, it was observed that sales decreased for the 2020 period, compared to 2019. Its reduction was approximately -27%, this reduction in sales was due to the lack of storage facilities. aluminum, wood and glass windows and doors at the time of the health crisis.